2019
DOI: 10.1002/stc.2424
|View full text |Cite
|
Sign up to set email alerts
|

Improved Kalman filter damage detection approach based on l p regularization

Abstract: Summary The conventional extended Kalman filter (EKF) for detecting structural damage with measured responses is a dynamic inverse problem. With the increase in size of the extended state vector, EKF suffers from low accuracy and convergence difficulty due to the ill‐condition of the inverse problem and increased computational error. To overcome the aforementioned drawbacks, an improved EKF method based on lp regularization (EKF‐lp) is proposed in this paper. In the proposed method, the sparse characteristic o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(7 citation statements)
references
References 51 publications
0
7
0
Order By: Relevance
“…The results showed that the computational efficiency (Table 9) of the proposed decision-level fusion was about 60% of the data-level fusion, while the efficiency of the D-S evidence fusion strategy was lower than that of the proposed decision-level fusion. The eigen perturbation and Kalman-filter-based SDD methods can process the structural vibration response signals in real time and identify the structural parameters [10,44]. Figure 16 shows the observed, real, and Kalman filter values of a vibration signal; it shows that the Kalman filter could effectively reduce the noise interference.…”
Section: Detection Results Of the Experimental Modelmentioning
confidence: 99%
“…The results showed that the computational efficiency (Table 9) of the proposed decision-level fusion was about 60% of the data-level fusion, while the efficiency of the D-S evidence fusion strategy was lower than that of the proposed decision-level fusion. The eigen perturbation and Kalman-filter-based SDD methods can process the structural vibration response signals in real time and identify the structural parameters [10,44]. Figure 16 shows the observed, real, and Kalman filter values of a vibration signal; it shows that the Kalman filter could effectively reduce the noise interference.…”
Section: Detection Results Of the Experimental Modelmentioning
confidence: 99%
“…Assuming that the structural system is time-invariant, the parameter evolution is modeled as. (7) where w θ denotes parameter noise with zero mean Gaussian covariance Q θ . Accordingly, an augmented state vector is defined as…”
Section: Minimum Variance Unbiased Joint Input-state Estimationmentioning
confidence: 99%
“…In this paper, the value of R ε will be determined using the L-curve. By plotting the summed mean squared values of the novelty term ∥ y k − ŷk ∥ 2 2 which is related to the regularized identification results of [7,43] can be obtained. The optimal value of R ε will be selected as the value at the corner of the L-curve, as shown in later figure 1.…”
Section: Covariance R ε Tuning Of the Proposed Pm2-umukfmentioning
confidence: 99%
See 1 more Smart Citation
“…For real-time analysis and online damage identification techniques, Kalman filter solutions [ 36 , 37 , 38 ] and eigen perturbation [ 39 , 40 ] could be implemented. In particular, industries have introduced eigen perturbation and Kalman filter approaches along with spectral decomposition methods for condition monitoring.…”
Section: Introductionmentioning
confidence: 99%